Metaphors in Contemporary Art - W. Mohd Apandi, Wan Nurhasyimah; Yan Ibrahim, Ahmad Rashdi (Idealogy Journal; Vol 3 No 2 (2018): Idealogy Journal (September 2018), 2018)
The use of metaphors in producing contemporary works of art is often used by artists to convey current ideas and issues in the era of contemporary visual art. The metaphor used is as a symbol for the meaning of a work in conveying the ideas and narrative of the story more creatively. In addition, the use of metaphors should be in line with the selection of subjects and meanings to be used and conveyed more accurately and effectively in the production of works to be seen and studied by art critics. Keywords: Photography, artistic elements, art work, consciousness.